4(y-2)+3(2y-1)=6(2y-1)=6(2y-3)

Simple and best practice solution for 4(y-2)+3(2y-1)=6(2y-1)=6(2y-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(y-2)+3(2y-1)=6(2y-1)=6(2y-3) equation:



4(y-2)+3(2y-1)=6(2y-1)=6(2y-3)
We move all terms to the left:
4(y-2)+3(2y-1)-(6(2y-1))=0
We multiply parentheses
4y+6y-(6(2y-1))-8-3=0
We calculate terms in parentheses: -(6(2y-1)), so:
6(2y-1)
We multiply parentheses
12y-6
Back to the equation:
-(12y-6)
We add all the numbers together, and all the variables
10y-(12y-6)-11=0
We get rid of parentheses
10y-12y+6-11=0
We add all the numbers together, and all the variables
-2y-5=0
We move all terms containing y to the left, all other terms to the right
-2y=5
y=5/-2
y=-2+1/2

See similar equations:

| X²+5=y/87 | | 6(-2g-1)=-13g+2) | | 3b-7+2(b-1)=2b-3 | | (X-3)•(2x-1)+(x+2)•(2x+1)=17 | | 8x+24=9x+12 | | x+x+1.75x=220 | | x+x+2x=220 | | x+2x+3x=220 | | 7w+5-8w=12-3w | | 5/8c=60/8 | | -14-(-42)=x/11 | | 5/8c=60/4 | | 5x=1.6= | | 2/3x-5=-1/2x+2 | | 2/3y-9=7/3-19 | | 2/3y-9=7/3-18 | | 2x+3=3/4x-2 | | 6-7/9x=3/4 | | -3/5x-1=4 | | X+(.06)x=125 | | 4/x-5-1/3=-8/3x-15 | | 30=x2+x | | -3y-6(5y-3)=1-2(-3-y) | | x^2+5x-15=7x | | 12p-3=8 | | 6900=1.0825x | | 4r²+20+25=0 | | F(x)=-7+3 | | 12/x=25/100 | | 8x-11=x+12 | | 2y-×^+3=0 | | 0=1.5(t^2)-6t+3 |

Equations solver categories